FRET based quantification and screening technology platform for the interactions of leukocyte function-associated antigen-1 (LFA-1) with intercellular adhesion molecule-1 (ICAM-1). - Sandeep Chakraborty; David Núñez; Shih-Yang Hu; María Pilar Domingo; Julian Pardo; Artashes Karmenyan; Eva Ma Gálvez; Arthur Chiou (PLoS ONE, 2014)
The interaction between leukocyte function-associated antigen-1(LFA-1) and intercellular adhesion molecule-1 (ICAM-1) plays a pivotal role in cellular adhesion including the extravasation and inflammatory response of leukocytes, and also in the formation of immunological synapse. However, irregular expressions of LFA-1 or ICAM-1 or both may lead to autoimmune diseases, metastasis cancer, etc. Thus, the LFA-1/ICAM-1 interaction may serve as a potential therapeutic target for the treatment of these diseases. Here, we developed one simple 'in solution' steady state fluorescence resonance energy transfer (FRET) technique to obtain the dissociation constant (Kd) of the interaction between LFA-1 and ICAM-1. Moreover, we developed the assay into a screening platform to identify peptides and small molecules that inhibit the LFA-1/ICAM-1 interaction. For the FRET pair, we used Alexa Fluor 488-LFA-1 conjugate as donor and Alexa Fluor 555-human recombinant ICAM-1 (D1-D2-Fc) as acceptor. From our quantitative FRET analysis, the Kd between LFA-1 and D1-D2-Fc was determined to be 17.93±1.34 nM. Both the Kd determination and screening assay were performed in a 96-well plate platform, providing the opportunity to develop it into a high-throughput assay. This is the first reported work which applies FRET based technique to determine Kd as well as classifying inhibitors of the LFA-1/ICAM-1 interaction.